Vitamin D level in patients with type 1 diabetes and its relation to tissue transglutaminase immunoglobulin A antibodies - Asmaa K Ahmad; Omnia A Hussein; Ahmed A Saedii (SpringerOpen, 2019)
Introduction Type 1 diabetes mellitus (T1DM) is a lifelong metabolic disorder, which accounts for ∼10% of all cases of diabetes. Vitamin D deficiency is extensively studied in the pathogenesis of T1DM. Vitamin D regulates both innate and adaptive immunity, and this indicates its potential role in preventing and treating T1DM. T1DM is also associated with celiac disease which is an autoimmune-mediated, chronic inflammatory disorder of the small intestine. Vitamin D deficiency has been described in patients with celiac disease and T1DM. Aim The study's primary aim was to investigate the 25-hydroxyvitamin D [25(OH)D] level in patients with T1DM and relation between vitamin D level and the presence or absence of tissue transglutaminase immunoglobulin A [tTG (IgA)] antibodies. Patients and methods The study estimated 25(OH)D level in 75 patients with T1DM and 15 healthy participants. It also studied the relation between vitamin D level and the presence or absence of tTG (IgA) antibodies. Results Patients with T1DM had significantly lower level of 25(OH)D (82.7%) compared with control participants (46.7%) (P=0.003). In all, 5.3% of patients were positive for tTG (IgA) antibody, and antibody titer was significant higher in patients with T1DM, with mean of 1.57±3.38, compared with control participants, with mean of 0.31±0.07 (P=0.001). Vitamin D level was low in diabetic patients with positive tTG (IgA) antibody than diabetic patients with negative tTG (IgA) antibody, but this change did not achieve significant value. Conclusion Vitamin D deficiency is high in children and adolescents with T1DM. Its level was decreased in diabetic patients with positive tTG (IgA) antibody than diabetic patients with negative tTG (IgA) antibody.